2019
DOI: 10.1007/s00380-019-01541-8
|View full text |Cite
|
Sign up to set email alerts
|

Narrower QRS may be enough to respond to cardiac resynchronization therapy in lightweight patients

Abstract: A prolonged QRS duration (QRSd) is promising for a response to cardiac resynchronization therapy (CRT). The variation in human body sizes may affect the QRSd. We hypothesized that conduction disturbances may exist in Japanese even with a narrow (< 130 ms)-QRS complex; such patients could be CRT candidates. We investigated the relationships between QRSd and sex and body size in Japanese. We retrospectively analyzed the values of 338 patients without heart failure (HF) (controls) and 199 CRT patients: 12-lead el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, some published studies report a positive CRT response in patients with a narrow QRS complex. ey describe the efficacy of CRT, as well as the existence of dyssynchrony in patients with a narrow QRS complex [14,[20][21][22]. Varma et al reported efficacy in patients with a narrow QRS complex <130 ms from the EchoCRT trial and concluded that CRT may be beneficial in patients with HF with a narrow QRS and smaller ventricles [23].…”
Section: Crt In Patients With a Narrow Qrs Complexmentioning
confidence: 99%
“…However, some published studies report a positive CRT response in patients with a narrow QRS complex. ey describe the efficacy of CRT, as well as the existence of dyssynchrony in patients with a narrow QRS complex [14,[20][21][22]. Varma et al reported efficacy in patients with a narrow QRS complex <130 ms from the EchoCRT trial and concluded that CRT may be beneficial in patients with HF with a narrow QRS and smaller ventricles [23].…”
Section: Crt In Patients With a Narrow Qrs Complexmentioning
confidence: 99%